Azelastine potentiates antiasthmatic dexamethasone effect on a murine asthma model - Carlos D. Zappia; Ariadna Soto; Gina Granja‐Galeano; Ignacio Fenoy; Natalia Fernandez; Carlos A. Davio; Carina Shayo; Carlos P. Fitzsimons; Alejandra Goldman; Federico Monczor (Wiley, 2019)
Abstract Glucocorticoids are among the most effective drugs to treat asthma. However, the severe adverse effects associated generate the need for its therapeutic optimization. Conversely, though histamine is undoubtedly related to asthma development, there is a lack of efficacy of antihistamines in controlling its symptoms, which prevents their clinical application. We have reported that antihistamines potentiate glucocorticoids' responses in vitro and recent observations have indicated that the coadministration of an antihistamine and a synthetic glucocorticoid has synergistic effects on a murine model of allergic rhinitis. Here, the aim of this work is to establish if this therapeutic combination could be beneficial in a murine model of asthma. We used an allergen‐induced model of asthma (employing ovalbumin) to evaluate the effects of the synthetic glucocorticoid dexamethasone combined with the antihistamine azelastine. Our results indicate that the cotreatment with azelastine and a suboptimal dose of dexamethasone can improve allergic lung inflammation as shown by a decrease in eosinophils in bronchoalveolar lavage, fewer peribronchial and perivascular infiltrates, and mucin‐producing cells. In addition, serum levels of allergen‐specific IgE and IgG1 were also reduced, as well as the expression of lung inflammatory‐related genes IL‐4, IL‐5, Muc5AC, and Arginase I. The potentiation of dexamethasone effects by azelastine could allow to reduce the effective glucocorticoid dose needed to achieve a therapeutic effect. These findings provide first new insights into the potential benefits of glucocorticoids and antihistamines combination for the treatment of asthma and grants further research to evaluate this approach in other related inflammatory conditions.